2007
DOI: 10.4319/lo.2007.52.3.1046
|View full text |Cite
|
Sign up to set email alerts
|

Simulated light regimes affect feeding and metabolism of Antarctic krill, Euphausia superba

Abstract: The effect of different light regimes on physiological parameters (feeding activity, oxygen consumption, and activity of the metabolic enzyme malate dehydrogenase [MDH]) of Antarctic krill, Euphausia superba, was studied over 12 weeks under laboratory conditions. Krill were exposed to light-cycle regimes of variable intensity to simulate Southern Ocean summer, autumn, and winter conditions, respectively, using: (1) continuous light (LL; 200 lux max), (2) 12-h light and 12-h darkness (LD 12 : 12; 50 lux max), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 28 publications
1
56
2
Order By: Relevance
“…The maximum feeding activity of krill was only 20% (autumn) and 14% (winter) of summer rates (Meyer et al 2010). In addition, laboratory experiments have shown that feeding, metabolic activity (Teschke et al 2007), growth (Brown et al 2010) and gene expression (Seear et al 2009) of adult krill are aVected by light conditions in terms of diVerent photoperiod. In contrast, recent feeding data from low latitudes (e.g.…”
Section: Reduction In Physiological Function In Adultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The maximum feeding activity of krill was only 20% (autumn) and 14% (winter) of summer rates (Meyer et al 2010). In addition, laboratory experiments have shown that feeding, metabolic activity (Teschke et al 2007), growth (Brown et al 2010) and gene expression (Seear et al 2009) of adult krill are aVected by light conditions in terms of diVerent photoperiod. In contrast, recent feeding data from low latitudes (e.g.…”
Section: Reduction In Physiological Function In Adultsmentioning
confidence: 99%
“…Outlined the Wrst comprehensive view of krill overwintering strategies Quetin and Ross (1991) Winter sea ice extent Showed that recruitment success and, hence population size of krill are linked to extent and duration of winter sea ice cover, with low ice years related to poor recruitment Siegel and Loeb (1995) Antarctic photoperiod mediate metabolic winter depression in krill Demonstrated from Weld and laboratory studies the eVect of photoperiod on physiological function of krill Meyer et al (2010), Teschke et al (2007) 1925-1927, 1923-1939, 1950-1951Mackintosh (1972 -Aug 1978, 1981, 1985, 1986Ligowski (2000 Lipid content…”
Section: Introductionmentioning
confidence: 99%
“…During summer, genes controlling feeding, digestion and respiration, amongst others, are up-regulated compared with winter conditions (Seear et al 2009(Seear et al , 2012, and the light regime seems of paramount importance to trigger these adjustments of E. superba to the drastic seasonal changes in Antarctic waters. The presence of food alone is not sufficient to trigger feeding activity (Atkinson et al 2002;Teschke et al 2007). Recent research indicated that endogenous (inherent) mechanisms exist to synchronise the seasonal and circadian rhythmicity of metabolic and physiological output (Teschke et al 2007(Teschke et al , 2008(Teschke et al , 2011Mazzotta et al 2010), triggered by light (Seear et al 2009;Teschke et al 2011;Brown et al 2013).…”
Section: Original Papermentioning
confidence: 99%
“…The presence of food alone is not sufficient to trigger feeding activity (Atkinson et al 2002;Teschke et al 2007). Recent research indicated that endogenous (inherent) mechanisms exist to synchronise the seasonal and circadian rhythmicity of metabolic and physiological output (Teschke et al 2007(Teschke et al , 2008(Teschke et al , 2011Mazzotta et al 2010), triggered by light (Seear et al 2009;Teschke et al 2011;Brown et al 2013). On the other hand, it was clearly shown in short-term starvation experiments that food availability does play a role: even after only 18 days without food, krill switched to a mode that reduced energy consumption and initiated consumption of body lipids (Atkinson et al 2002;Auerswald et al 2009).…”
Section: Original Papermentioning
confidence: 99%
See 1 more Smart Citation